A psychological perspective on entrepreneurship and innovation in universities: The role of educators and tutors in enhancing motivation, interest, and academic success - Qian Li; Zhaoping Zhang; Shien Xiao (Acta Psychologica)
A psychological perspective on entrepreneurship and innovation in universities underscores the significant role of educators and tutors in enhancing students' motivation, interest, and academic success. This study aims to assess the motivation, interest, and academic performance of students studying entrepreneurship in two distinct groups: one utilizing an innovative approach involving interaction with an educator and tutor from a real company, and the other employing a traditional teaching method. It enrolled 320 third-year students, who learned entrepreneurship in a Chinese university. The research tools were the Academic Motivation Scale (AMS) and the Interest in Entrepreneurship and Future Aspirations Questionnaire. The authors also considered the final annual grades in Entrepreneurship. Results highlighted the profound and multifaceted impact of the developed tutor-led approach in promoting increased motivation, interest, and performance in the intervention group. These results not only enrich the academic discourse on entrepreneurial education involving educators and tutors but also offer practical recommendations for instructors and educational institutions to enhance their pedagogical strategies. Future research prospects include exploring the complex dynamics of tutor interventions, their long-term impact, and addressing the limitations of current studies within the context of a psychological perspective on entrepreneurship and innovation in universities.